PENGEMBANGAN E-BOOK INTERAKTIF SEJARAH SENAPELAN SEBAGAI SUMBER BELAJAR SEJARAH LOKAL YANG MENARIK - Darmayani, Sri; Suroyo (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2025)
This research aims to develop an interactive e-book that presents the history of Senapelan as an interesting and educative learning resource. The history of Senapelan, which is rich in culture and tradition, has great potential to become relevant teaching material in local history learning. This interactive e-book is designed by integrating multimedia elements, such as text, images, videos, and quizzes, to increase student involvement in the learning process. The methodology used includes requirements analysis, content planning, design, and user testing. The trial results showed that the interactive e-book was effective in increasing students' understanding of the history of Senapelan and sparking their interest in learning local history. Students report a more enjoyable and interactive learning experience, which contributes to increased motivation and engagement. This research concludes that interactive e-books not only function as an interesting learning resource, but also as a tool that supports teaching for teachers. Thus, it is hoped that the development of this interactive e-book can become a model for implementing more innovative and relevant history learning in the digital era.